Systematic review indicates postnatal growth in term infants born small‐for‐gestational‐age being associated with later neurocognitive and metabolic outcomes. (15th May 2017) - Castanys‐Muñoz, Esther; Kennedy, Kathy; Castañeda‐Gutiérrez, Eurídice; Forsyth, Stewart; Godfrey, Keith M.; Koletzko, Berthold; Ozanne, Susan E.; Rueda, Ricardo; Schoemaker, Marieke; van der Beek, Eline M.; van Buuren, Stef; Ong, Ken K.
Abstract: We systematically reviewed papers published in English between 1994 and October 2015 on how postnatal weight gain and growth affect neurodevelopment and metabolic outcomes in term‐born small‐for‐gestational‐age (SGA) infants. Two randomised trials reported that enriched infant formulas that promoted early growth also increased fat mass, lean mass and blood pressure (BP), but had no effect on early neurocognitive outcomes. Meanwhile, 31 observational studies reported consistent positive associations between postnatal weight gain and growth with neurocognitive outcomes, adiposity, insulin resistance and BP. Conclusion: Few intervention studies exist, despite consistent positive associations between early growth and neurocognition in term‐born SGA infants.